Adenocarcinoma of the Colon Disguised as Abdominal Wall Abscess: Case Report and Review of the Literature - L. Attar; N. Trabulsi; A. A. Maghrabi; M. Nassif (Case Reports in Surgery)
Introduction. Abdominal wall invasion by cancerous cells arising from the colon with an overlying secondary infection that presents as an abdominal wall abscess has been encountered previously, but such a symptom is rarely the first presentation of colon cancer. There are very few cases reported in the literature. Case Presentation. In this case report, we present a case of a 66-year-old male presenting with abdominal wall abscess that was refractory to treatment. The patient later was found to have an abdominal wall invasion by an underlying colonic carcinoma. Conclusion. The purpose of this review is to set forth the proper approach when encountering such cases and emphasize on the significance of keeping a high index of suspicion. We also highlight the need for utilizing proper diagnostic imaging modalities prior to invasive intervention.